2007
DOI: 10.1002/ijc.23037
|View full text |Cite
|
Sign up to set email alerts
|

Family history of urogenital cancers in patients with bladder, renal cell and prostate cancers

Abstract: Family history of urogenital cancers has been associated with an increased risk of cancer at the same sites. To evaluate the risks of bladder, prostate and renal cell neoplasms for family history of urogenital cancers in first-degree relatives, we analysed data from a case-control study conducted in northern Italy between 1985 and 1992 and including a total of 1,356 incident, histologically confirmed cancer cases: 727 bladder, 348 renal cell and 281 prostate cancer cases. Controls were 1,067 patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 43 publications
5
32
0
1
Order By: Relevance
“…Increased risk of renal cancer has been associated with a family history of kidney cancer in most previous case -control (Mellemgaard et al, 1994;Schlehofer et al, 1996;Gago-Dominguez et al, 2001;Negri et al, 2006;Clague et al, 2009) and cohort studies (Goldgar et al, 1994;Czene and Hemminki, 2002;Gudbjartsson et al, 2002;Clague et al, 2009), although results for some are null or not statistically significant (McLaughlin et al, 1984;Kreiger et al, 1993;Hung et al, 2007;Randi et al, 2007). The reported excess risks generally ranged from two-to five-fold for both study designs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increased risk of renal cancer has been associated with a family history of kidney cancer in most previous case -control (Mellemgaard et al, 1994;Schlehofer et al, 1996;Gago-Dominguez et al, 2001;Negri et al, 2006;Clague et al, 2009) and cohort studies (Goldgar et al, 1994;Czene and Hemminki, 2002;Gudbjartsson et al, 2002;Clague et al, 2009), although results for some are null or not statistically significant (McLaughlin et al, 1984;Kreiger et al, 1993;Hung et al, 2007;Randi et al, 2007). The reported excess risks generally ranged from two-to five-fold for both study designs.…”
Section: Discussionmentioning
confidence: 96%
“…Smoking, obesity, and hypertension are primary risk factors that may explain half of all RCC diagnoses in the United States (Benichou et al, 1998;Chow and Devesa, 2008). RCC risk has been examined in relation to familial history of cancer in a number of epidemiological studies (McLaughlin et al, 1984;Kreiger et al, 1993;Goldgar et al, 1994;Mellemgaard et al, 1994;Schlehofer et al, 1996;Gago-Dominguez et al, 2001;Hemminki, 2002, 2003;Gudbjartsson et al, 2002;Negri et al, 2006;Hung et al, 2007;Randi et al, 2007;Clague et al, 2009). Many of these studies have shown a positive association with a family history of cancer (Goldgar et al, 1994;Mellemgaard et al, 1994;Schlehofer et al, 1996;Gago-Dominguez et al, 2001), particularly when the affected relative is a sibling (Czene and Hemminki, 2002;Gudbjartsson et al, 2002;Negri et al, 2006;Hung et al, 2007;Clague et al, 2009).…”
mentioning
confidence: 99%
“…[31][32][33][34] There is a significantly increased risk of bladder cancer among firstdegree relatives of individuals who have bladder cancer, with an earlier age of disease onset. [35][36][37] In a large twin study, environmental factors were estimated to contribute a significant 69% to bladder cancer risk, whereas inherited genetic factors contributed a nonsignificant 31% of risk. 38 Attention has been given to the NAT2 slow acetylator and GSTM1-null genotypes as potential familial risk factors.…”
Section: Bladder Cancer Carcinogenesismentioning
confidence: 99%
“…Table 4 summarizes pertinent details of 9 case-control and 4 cohort studies in which family history of TCCUT was quantitatively evaluated as a bladder cancer risk factor. [12][13][14][15][16][17][18][19][20][21][22][23][24] These studies varied widely in sample size, quality of design and analysis, inclusion/exclusion of upper urinary tract sites, and the extent to which reported cancers were objectively documented, but are surprisingly similar in their estimated risk ratios. These range from 1.2 to 6.1 among male and female cases combined, with most of the results clustering between 1.4 and 1.9.…”
Section: Case Reports Of Familial Tccutmentioning
confidence: 99%
“…[2,7] Common variants in low-penetrance genes involved in the metabolism of environmental toxins have been shown to modify individual susceptibility to bladder carcinogens. [2] Furthermore, a genetic predisposition to bladder cancer is suggested by the occurrence of TCCUT in several Mendelian disorders [8][9][10][11], epidemiologic studies showing that a positive TCCUT family history increases bladder cancer risk [12][13][14][15][16][17][18][19][20][21][22][23][24], and a limited number of case reports describing multiple-case TCCUT families. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Therefore, both genetic and environmental factors play a role in the development of bladder and related urinary tract cancers.…”
Section: Introductionmentioning
confidence: 99%